AVALIAÇÃO PRELIMINAR DA QUALIDADE DAS ÁGUAS DO ARROIO ESPINHO, IJUÍ, RS, E DA OCORRÊNCIA DE COLIFORMES RESISTENTES A ANTIMICROBIANOS - Amorin, André L. B.; Almeida, Maris L.; Bellinaso, Maria D. L. (Salão do Conhecimento, 2013)
Resumo